Modelling dan NVH Analysis of EMU Motor Car - Syahrul Fadhil (NIM : 13113040), Muhammad
The increasing number of passengers using Soekarno–Hatta International Airport has caused traffic jam on toll road connecting it to Jakarta. Soekarno–Hatta International Airport Rail Link (SHIARL) is created to decrease the required time to reach the airport from Jakarta. The rolling stock used is electrical multiple unit (EMU) which is manufactured by PT Industri Kereta Api (Persero). To ensure passenger comfort, it is necessary to study NVH comfort aspects of the EMU. In this research, the vibrational comfort aspect of M2 carriage of the EMU is studied by looking the carbody structure’s natural frequency of the M2 carriage of the EMU, especially in its first vertical and lateral bending mode. The natural frequencies are calculated by conducting modal analysis. Besides that, spectrum analysis is done to see the acceleration response qualitatively. Modal analysis and spectrum analysis are done using Mechanical APDL program. Simulation results show that the first vertical and lateral bending natural frequencies of the structure are 19.397 Hz and 8.350 Hz, respectively. The minimum first vertical and lateral bending natural frequency of 10 Hz is required for passenger comfort. Therefore, the lateral vibrational comfort is not achieved. The biggest acceleration response occured at the center of the carbody. Further researches on measuring natural frequencies experimentally and measuring ride index in operational condition are needed to verify this research results.